ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA KERAMBA IKAN MAS DI KECAMATAN BABIRIK KABUPATEN HULU SUNGAI UTARA - Arief Hidayatullah (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
The analysis used in this experiment was is the the analysis of Cobb-Douglas production function and elasticity of production. The results obtained were F test results stating that all variable number of cages, seed, feed, and labor simultaneously significant effect on the production of carp. Based on the coefficient of determination showed that 89% variation amount of production can be explained by a variable number of cages seed, feed and labor. While 11% is influenced by other variables not included in the regression model. T test results stated that the factor of seed and feed real and significant effect on the production of carp while the number of cages and a factor of labor is not significant and not significant to the production of carp. The elasticity of the production number cages, seed, feed, and labor respectively (-0.983), (0.600) (0.221) (0.441) which means elastsitas number of cages in the region of production III and elasticity of seed, feed and energy working in the region of production II. Suggestions in this study were (1) should farmers carp determine the factors of production that significantly affect the production of carp so that farmers can see the production factors which need to be considered both quantity and quality, (2) should need counseling for farmers on the use of factors of production enterprises an efficient carp cages primarily on the number of cages in a single use of cages without reducing the use of seeds. Keywords: Goldfish, Regression Model, Elasticity Production